Trend Research of Polymer Gel Dosimetry: A Systematic Review - Aris Doyan; Susilawati Susilawati; Syarful Annam; Teguh Ardianto; Muhammad Ikhsan; Nurul Rachma Ardianti; Hamidi Hamidi (Balai Publikasi Indonesia, 2025)
Polymer gel dosimeters are fabricated from radiation sensitive chemicals which, upon irradiation, polymerize as a function of the absorbed radiation dose. These dosimeters, which uniquely record the radiation dose distribution in three-dimensions (3D), have specific advantages when compared to one-dimensional dosimeters, such as ion chambers, and two-dimensional dosimeters, such as film. This research aims to identify and analyze research trends of Polymer gel dosimeters. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2016-2025 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research Polymer gel dosimeters that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2016 to 2025 has experienced ups and down. There are many documents in the form of articles, chapters, proceeding, and edited books that discuss research about Polymer gel dosimeters. Key words that are often used in research about it are Magnetic Resonance Imaging, MRI, Monte carlo simulation, Characterization, Fricke gel, Polymerization, etc.